Clinical and OCT features of different types and stages of diabetic optic neuropathy - P.A. Bezditko; M.A. Karliychuk (Ukrainian Society of Ophthalmologists, 2018)
Background: The advent of optical coherence tomography (OCT) has offered new opportunities for differential diagnosis of diabetic optic neuropathy (DON). Purpose: To identify clinical and OCT features of different types and stages of DON. Materials and Methods: A total of 575 patients (1150 eyes) with type 2 diabetes mellitus (T2DM) were included in the prospective analysis of the features of optic nerve damage. For comparison, we used data from a group of 50 age- and sex-matched healthy control patients. In addition to routine ocular examination, patients underwent ophthalmochromoscopy, OCT of the retina and optic nerve, and electrical physiological studies. Results: In diabetic papillopathy, anterior ischemic DON, and degenerative-, advanced-, mild-, and subclinical-stage axial DON groups, mean ganglion cell complex focal loss volume values were 21.7, 20.5, 17.3, 13.4, 10.3, and 7.5 times higher, respectively, than in controls. In diabetic papillopathy, anterior ischemic DON, and advanced-stage axial DON groups, mean peripapillary retinal thickness values were 92.2%, 84.7%, and 38.7% higher, respectively, than in controls, whereas in subclinical-, mild-, and degenerative-stage axial DON groups, the values were 8.0%, 13.8%, and 20.5% lower, respectively, than in controls. Conclusion: We have identified clinical and OCT features of different types and stages of DON in patients with T2DM.